Issue reframing by parties: The effect of issue salience and ownership. (July 2019) - Lefevere, Jonas; Sevenans, Julie; Walgrave, Stefaan; Lesschaeve, Christophe
Issue reframing occurs when parties, while addressing an issue, shift the frame toward other policy domains. The literature has found that party issue framing affects how voters think about issues, yet scholars remain largely in the dark as to when and how parties frame issues. The study at hand theorizes and investigates when and how parties reframe issues in their external communication. Drawing on novel Belgian data about parties' official stances regarding a large number of policy issues combined with their verbal argumentation of why they took this exact position, we test a new theory about the drivers and mechanisms of issue reframing. We find that parties reframe issues in terms of policy domains that are both salient to the general public and that are salient to the party itself—meaning that it has a history of devoting attention to the policy domain and "owns" it.